2016
DOI: 10.1002/jnr.23854
|View full text |Cite
|
Sign up to set email alerts
|

Do microglia play a role in sex differences in TBI?

Abstract: Traumatic brain injury (TBI) is one of the leading causes of morbidity and mortality for both males and females and is, thus, a major focus of current study. Although the overall death rate of TBI for males is roughly three times higher than that for females, males have been disproportionately represented in clinical and preclinical studies. Gender differences are known to exist in many neurologic disorders, such as multiple sclerosis and stroke, and differences appear to exist in TBI. Furthermore, it is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 63 publications
1
53
0
4
Order By: Relevance
“…This can be attributed, at least partially, to astrocytes and microglia, as recently reviewed (Caplan et al, 2017). Gonadal steroid hormones such as progesterone and estradiol are directly involved in the glial response under injury conditions in and during development (Lenz and McCarthy, 2015).…”
Section: Microglia Activation States In Tbimentioning
confidence: 84%
“…This can be attributed, at least partially, to astrocytes and microglia, as recently reviewed (Caplan et al, 2017). Gonadal steroid hormones such as progesterone and estradiol are directly involved in the glial response under injury conditions in and during development (Lenz and McCarthy, 2015).…”
Section: Microglia Activation States In Tbimentioning
confidence: 84%
“…While we can detect sex-differences in lesion volume acutely after injury, we observe identical brain tissue loss at 1-month post-injury. Previous clinical and animal studies have demonstrated that sex-differences in mortality and functional outcomes exist after TBI (Caplan et al 2017), and the use of hormone-based therapies in preclinical studies clearly show that female sex hormones, estrogen, and progesterone, are protective after TBI (Engler-Chiurazzi et al 2016; Stein 2015). One of the major targets of estrogen and progesterone is the inflammatory response, and in vitro and in vivo studies demonstrate that these hormones can attenuate microglial activation and pro-inflammatory cytokine release (Arevalo et al 2013; Belcredito et al 2001; Bruce-Keller et al 2007; Bruce-Keller et al 2000; Crain et al 2013; Dimayuga et al 2005; Goodman et al 1996; Habib and Beyer 2015; Sawada et al 2000; Vegeto et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review highlights the sparse and controversial background literature on sex-differences in mortality and functional outcome after TBI (Caplan, Cox, & Bedi, 2017), and it is clear that more studies are required to understand how sex affects neuroinflammatory mechanisms and outcomes after injury. However, the vast majority of the experimental preclinical TBI studies looking at the inflammatory response to TBI have been conducted using male animals.…”
mentioning
confidence: 99%
“…The literature looking at the impact of sex disparities is limited (Caplan et al, 2017). In a recent study, mild-moderate CCI caused cortical microglia/macrophage activation in male mice peaking between 1 and 7 days.…”
Section: Introductionmentioning
confidence: 99%